The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10517-016-3559-z
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-Epithelial Transition in Culture of Stromal Progenitor Cells Isolated from the Liver of a Patient with Alcoholic Cirrhosis

Abstract: The cells isolated from biopsy specimen of a patient with alcoholic liver cirrhosis and cultured under standard conditions for obtaining stromal cell culture clearly diverged during early passages into two morphologically and phenotypically different subtypes: epithelial and mesenchymal. Mesenchymal cells expressed CD90 and CD44 and epithelial cells expressed CD166, CD227, and hepatocyte growth factor receptor Met. Starting from passage 6, the culture underwent spontaneous morphological changes and by passages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…We [29], as well as other authors [30,31], obtained liver MSCs from liver biopsy material by tissue disintegration and subsequent processing with collagenase. The resulting cell suspension, without any additional manipulations, was placed in uncoated culture flasks and incubated in the medium for the cultivation of MSCs (DMEM + 10–20% FBS).…”
Section: Methods Of Isolation Of Human Liver Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…We [29], as well as other authors [30,31], obtained liver MSCs from liver biopsy material by tissue disintegration and subsequent processing with collagenase. The resulting cell suspension, without any additional manipulations, was placed in uncoated culture flasks and incubated in the medium for the cultivation of MSCs (DMEM + 10–20% FBS).…”
Section: Methods Of Isolation Of Human Liver Mscsmentioning
confidence: 99%
“…Our gene expression microarray data show that MSCs isolated from the liver of patients with fibrosis or cirrhosis express several liver-specific genes: ribonuclease RNase A family 4 ( RNASE4 ), CYP1A2 , γ-glutamyl transpeptidase ( GGT1 ), and glutamine synthase ( GLUL )—at a low level; CYP1B1 —at a relatively high level; a very high level of expression was observed only for the NNMT gene encoding the nicotinamide N -methyltransferase. Albumin, α-phetoprotein ( AFP ), and hepatocyte nuclear factor-4 ( HNF4A ) were not expressed in our liver MSCs both at the protein level [29] and at the mRNA level. At the same time, expression of the c-Met hepatocyte growth factor receptor was detected by us in 60% of cells in the liver MSC population by flow cytometry [29] as well as at the transcriptome level (see Table 1).…”
Section: Morphology and Phenotype Of Human Liver Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, that there are discrepancies in the data presented by authors in the literature concerning the pattern of markers expressed by epithelial and mesenchymal afterbirth cells [109,181]. Native human afterbirth cells share some phenotypic features comparable with human hepatic multipotent stem cells (hHpSC) and bipotent hepatoblasts: EpCAM, CK19, CD133 [17,27,35,181], adult multipotent stem cells expressing mesenchymal markers: CD44, CD73, CD90, CD105, CK19, SSEA-4, NANOG, OCT-4 [15,52,66,67,181,[53][54][55][56][57][58][59][60] and adult bipotent hepatic progenitor cells (HPC): DLK-1 [78,184]. EpCAM expression, characteristic of hepatoblasts, but not of mesenchymal liver cells, has been confirmed in afterbirth cells only in few studies [181,[183][184][185].…”
Section: Discussionmentioning
confidence: 97%
“…Jones et al [24] reported that bovine BMSCs are positive for expression of CD166. In addition, bovine LMSCs are negative for expression of CD166 but positive for expression of CD44, CD29, CD73, CD90, and CD106 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. +( 32)…”
Section: Human Lmscs and Human Bmscsmentioning
confidence: 99%